“The significance of cardiac magnetic resonance imaging in detection and monitoring of the treatment efficacy of heart involvement in eosinophilic granulomatosis with polyangiitis patients” - Fijolek, Justyna; Wiatr, Elzbieta; Gawryluk, Dariusz; Nowicka, Urszula; Martusewicz-Boros, Magdalena Maria; Kober, Jaroslaw; Piotrowska-Kownacka, Dorota; Roszkowski-Sliz, Kazimierz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
BACKGROUND.  Cardiac magnetic resonance imaging (CMRI) has emerged as a sensitive and non-invasive technique in the  evaluation of cardiac lesions in eosinophilic granulomatosis with polyangiitis (EGPA) patients.OBJECTIVES: To evaluate the ability of CMRI to detection and monitoring of the treatment efficacy  in EGPA patients with cardiac involvement.METHODS. To the retrospective-prospective study were enrolled 33 cardiac involvement EGPA patients. In 19 of them CMRI at the moment of diagnosis was performed,  in 14 – CMRI  after treatment was made, when this method  was available - in this group the cardiac involvement was based on the clinical findings.  All patients were treated with corticosteroids (CSs) and/or cyclophosphamide (CY). In the first group the control CMRI after one year of  treatment was performed, but in the second group the time from the end of the treatment to execution of  CMRI was 2-5 years.RESULTS. All patients had  heart injury in CMRI. Myocardial edema  was present in 87.8% cases, 54.5% of patients had perfusion defects  and in all - late gadolinium enhancement was observed. Control CMRI was performed in 32 cases. Improvement was observed in  81%  of patients – in 11% of them all lesions  undergone  completely remission and in  35% of them evolution to global fibrosis was found. In 7% of patients stabilization was achieved and in 12% - progression  was observed.CONCLUSIONS. CMRI is a sensitive method detecting cardiac lesions in EGPA patients. It helps to detect patients, who need combined therapy and helps evaluate the therapeutic effect.